Engaging Persuasion: What Should Undergraduate Students Enrolled in a Persuasion Course Learn? - Stephen K. Hunt; Kevin Meyer (Central States Communication Association, 2019)
In our daily activities we are bombarded with persuasive messages. From advertising on mass and social media to interactions with friends, we are constantly exposed to attempts to change or reinforce our attitudes, values, beliefs, and behaviors. Conversely, we routinely attempt to influence others and gain their compliance through persuasive attempts of our own. Without question, persuasion is a central feature of virtually every aspect of human communication and is found wherever we find people communicating. Fortunately, scholars have developed a great number of empirically tested persuasive techniques, strategies, and theories that can help students become effective producers and consumers of persuasive messages. This article outlines the foundations, content areas, and applied assignments appropriate for an undergraduate persuasion course. In addition, we outline several pedagogical issues for instructors to consider.